Pathways to Quality: Nurse Work Environment, Unfinished Nursing Care, Job Satisfaction, and The Electronic Health Record - Terry Jones; Caitlin Campbell; Aoyjai Montgomery; Colleen Pogue; Marianne Baernholdt; Patricia Patrician (KHD-Production, 2023)
Better nurse work environments are associated with patient and nurse outcomes reflecting nursing care quality. Mechanisms through which the work environment influences nursing care quality are not well documented. Unfinished nursing care, electronic health records, and job satisfaction may be involved. Clear mechanistic pathways that explain how these variables might interact to influence care quality are lacking. This study examined how satisfaction with the electronic health record, unfinished care, the work environment, and job satisfaction collectively affect nursing care quality. A secondary analysis of cross-sectional data was performed using survey data collected from inpatient hospital staff nurses in a single U.S. state. Survey responses (n=916) were analyzed using bivariate correlations and path analysis. Moderate bivariate correlations were documented among all study variables. However, smaller effects were identified in the full path analysis model. The nurse work environment had direct and indirect effects (through unfinished nursing care and job satisfaction) on nursing care quality. Satisfaction with the electronic health records affected nursing care quality indirectly through an inverse relationship with unfinished nursing care. More research is needed to better understand the mechanisms through which the electronic health record influences the nurse work environment and nursing care quality are needed.